Typology of Ordinary Wastewater Treatment Technologies Installed in Costa Rica - Centeno Mora, Erick (2019)
This paper presents a profile of municipal wastewater treatment plants in Costa Rica, comparing it with those of other Latin American and Caribbean countries. By collecting data from 47 plants operated by public entities, complemented by the analysis of a sample of 382 projects which had requested construction permits between 2011 and 2016, it was possible to characterize wastewater treatment in Costa Rica in terms of capacity and technology trends. Results show that more than 90% of the plants operated by public entities can be considered as small, with 70% designed for flows of less than 5.0 L/s. With regard to the projects which had requested construction permits, more than 90 % of the plants were designed for flows of less than 5.0 L/s, and 84% were systems for private condominium projects. Use of activated sludge in treatment technology was found in 57% of the systems operated by public entities and in 98% the projects which had requested construction permits. Costa Rica has a higher proportion of small capacity plants (Q < 25 L/s) and uses activated sludge more frequently than the other Latin American and Caribbean countries that were analyzed in this study. These two conditions can result in higher operating costs, and it is recommended to review this practice in order to promote universal and more sustainable sanitation.